Small extracellular vesicle-mediated ITGB6 siRNA delivery downregulates the αVβ6 integrin and inhibits adhesion and migration of recipient prostate cancer cells. Issue 1 (31st December 2022) - Krishn, Shiv Ram; Garcia, Vaughn; Naranjo, Nicole M.; Quaglia, Fabio; Shields, Christopher D.; Harris, Maisha A.; Kossenkov, Andrew V.; Liu, Qin; Corey, Eva; Altieri, Dario C.; Languino, Lucia R.
ABSTRACT: The αVβ6 integrin, an epithelial-specific cell surface receptor absent in normal prostate and expressed during prostate cancer (PrCa) progression, is a therapeutic target in many cancers. Here, we report that transcript levels of ITGB6 (encoding the β6 integrin subunit) are significantly increased in metastatic castrate-resistant androgen receptor-negative prostate tumors compared to androgen receptor-positive prostate tumors. In addition, the αVβ6 integrin protein levels are significantly elevated in androgen receptor-negative PrCa patient derived xenografts (PDXs) compared to androgen receptor-positive PDXs. In vitro, the androgen receptor-negative PrCa cells express high levels of the αVβ6 integrin compared to androgen receptor-positive PrCa cells. Additionally, expression of androgen receptor (wild type or variant 7) in androgen receptor-negative PrCa cells downregulates the expression of the β6 but not αV subunit compared to control cells. We demonstrate an efficient strategy to therapeutically target the αVβ6 integrin during PrCa progression by using short interfering RNA (siRNA) loaded into PrCa cell-derived small extracellular vesicles (sEVs). We first demonstrate that fluorescently-labeled siRNAs can be efficiently loaded into PrCa cell-derived sEVs by electroporation. By confocal microscopy, we show efficient internalization of these siRNA-loaded sEVs into PrCa cells. We show that sEV-mediated delivery of ITGB6 -targeting siRNAs into PC3 cells specifically downregulates expression of the β6 subunit. Furthermore, treatment with sEVs encapsulating ITGB6 siRNA significantly reduces cell adhesion and migration of PrCa cells on an αVβ6-specific substrate, LAP-TGFβ1. Our results demonstrate an approach for specific targeting of the αVβ6 integrin in PrCa cells using sEVs encapsulating ITGB6 -specific siRNAs.